Astroglypha passiflora Downey 1971, n. comb. - Mah, Christopher L. (Zenodo, 2021)
Astroglypha passiflora Downey, 1971 n. comb. Figure 8A–E Downey 1971: 49; 1973: 65; Clark & Downey 1992: 283, 284; A.M. Clark 1993: 354 (checklist). Taxonomic discussion. The specimen observed below is the first sampled from the eastern North Atlantic and represents an atypically small individual (R=0.5). Although only single papular pores are present, the R:r ratio and other features imply growth related characters rather than the presence of the Pacific species in the North Atlantic. In situ v ideo images of this species were captured by the NOAA ship Okeanos Explorer during the Oceano Profundo expedition in April 2015. Both images showed this species on limestone substrate adjacent to sponges, which are a possible prey item. Occurrence. Irving Bank, North Atlantic . Bahamas, Gulf of Mexico , Straits of Florida, Puerto Rico , Yucatan Channel 198– 549 m . Material examined. MNHN IE-2013-6727. Banc Irving, North Atlantic, 31º54′N, 28º3′W, 275 m. Coll. N. Ameziane aboard N/ O le Suroit , SEAMOUNT 2, DW 215, 1 dry spec. R =0.5, r=0.2. USNM 1226477. South of Atchafalaya Bay, Louisiana, Gulf of Mexico, North Atlantic, 27º45′N, 91º18′W, 549 m. Coll. R / V Oregon . 4 dry specs. R =2.6, r=0.7; R =1.8, r=0.5; R =1.7, r=0.6; R =1.3, r=0.5. USNM 1233542. Yucatan Channel, Cozumel Island, Mexico, 20º30′N, 86º14′W, 311– 329 m. Coll. R / V Oregon , 12 June 1964, 4 dry spec. R =1.8, r=0.6; R =1.6, r=0.7; R =2.0, r=0.7; R =2.1, r=0.7. USNM 1233829. Yucatan Channel, Cozumel Island, Mexico, 20º30′N, 86º14′W, 311– 329 m. Coll. R / V Oregon , 12 June 1964, 1 dry spec. R =2.1, r=0.8. USNM E19256. Straits of Florida, 24º22′N, 81º11′W, 198 m. Coll. R / V Gerda , 1 dry spec. R =2.4, r=0.8. Images examined. Pichincho area located ~ 33 miles west of Rincon, Puerto Rico, 300–600 m. EX1502 L3_ IMG_20150412 T194255 Z_ ROVHD _ASR_SPO.jpg ~ 22 miles W of Cabo Rojo, Puerto Rico, 300–600 m. EX1502 L3_IMG_20150415 T181913 Z_ ROVHD _ASR_COR_SP.jpg : Published as part of Mah, Christopher L., 2021, The East Pacific / South Pacific Boundary: New taxa and occurrences from Rapa Nui (Easter Island), New Caledonia and adjacent regions, pp. 401-450 in Zootaxa 4980 (3) on pages 421-423, DOI: 10.11646/zootaxa.4980.3.1, http://zenodo.org/record/4896889 : {"references": ["Downey, M. (1971) Two new species of the genus Tamaria (Echinodermata: Asteroidea) from the tropical western Atlantic. Proceedings of the Biological Society of Washington, 84 (5), 43 - 50.", "Downey, M. E. (1973) Starfishes from the Caribbean and the Gulf of Mexico. Smithsonian Contributions to Zoology, 126, 1 - 158. https: // doi. org / 10.5479 / si. 00810282.126", "Clark, A. M. & Downey, M. E. (1992) Starfishes of the Atlantic. Chapman & Hall, London, 794 pp.", "Clark, A. M. (1993) An index of names of recent Asteroidea. Part 2: Valvatida. Echinoderm Studies, 4, 187 - 366. https: // doi. org / 10.1201 / 9781003072553 - 4"]}